Macro- versus microscopic view on the electrokinetics of a water-membrane interface - Knecht, Volker (Langmuir : the ACS journal of surfaces and colloids, 2013)
Electrophoresis is an experimental method widely used to study electrostatic properties of interfaces. Here, we question the validity of the macroscopic theory for the planar geometry by Helmholtz and Smoluchowski by considering a POPC bilayer in an aqueous solution with 500 mM NaCl, using molecular dynamics simulations. We find that POPC shows positive electrophoretic mobility due to adsorption of sodium ions at the lipid headgroups. The theory assumes that the region in which the water density undergoes a transition from the bulk value to zero (interfacial width) is small compared to the Debye screening length. This separation of length scale is not fullfilled in the present case. Hence, contrasting the theory, we observe that the surface is not sharply defined, continuum hydrodynamics is not applicable, the effective viscosity in the double layer is increased compared to the bulk, and the zeta potential is dominated by the dipole potential. Our results might have widespread implications for interpretation of electrokinetic studies in general